ECHOES OF THE OLD COUNTRIES OR BRAVE NEW WORLDS? LEGAL RESPONSES TO REFUGEES AND ASYLUM SEEKERS IN AUSTRALIA AND NEW ZEALAND - Crock, Mary (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2001)
In spite of their colonial origins and their continuing ties with Great Britain and Europe, it is only recently that Australia and New Zealand have begun to think in global terms about immigration control and the challenges posed by asylum seekers. The experience of unauthorized migration in these two countries has been somewhat different. Nevertheless, both are now feeling the effects of the burgeoning industry of people smuggling. The closure of traditional migration routes throughout Europe brought about by the harmonization of laws and practice within the European Union may be one factor in the rise of unauthorized migration in the Asia Pacific region. While European laws and policies rarely rate a mention in the refugee discourse in this part of the world, the response to the mobile asylum seeker phenomenon reveals many resonances with the approaches adopted in the “old World” of the European Union – and, more recently, in the United States. This paper argues that, in Australia’s case, some “borrowings” from Europe and from North America have been inappropriate for this region. Far from evincing a commitment to global solutions and rationalized responses to humanitarian crises, the Australian initiatives suggest a country immersed in local concerns and self-interest. In spite of its tiny size and geographical isolation, the greater openness of New Zealand’s laws provides some interesting contrast material. Of equal interest, however, is the attention the world is beginning to pay to Australia’s asylum laws – most particularly those relating to the detention and removal of asylum seekers who come as unauthorized arrivals.